Pendekatan Ekspositoris tentang Kuliner Tionghoa Selatan di Kota Bandung dalam Penulisan Naskah Film Dokumenter “Jejak Rasa” - Vania Annora Martsa Awanti; Rinda Aunillah Sirait; Jimi Narotama Mahameruaji (Ekspresi : Publikasi Kegiatan Pengabdian Indonesia, 2026)
This study aims to examine the application of an expository approach in the scriptwriting of the documentary film "Jejak Rasa," which highlights Southern Chinese cuisine in Bandung as a representation of cultural acculturation. The background of this research is based on the declining interest of the younger generation in traditional culinary arts due to the influence of globalization and social media trends. The methods used included literature research, field observations, and interviews with relevant sources, such as culinary entrepreneurs and museum officials. The results show that the expository approach is effective in conveying information systematically, factually, and easily understood through the use of voice-over narration as the main direction of the story. Furthermore, the use of an implied first-person perspective creates an emotional connection between the audience and the material presented. This documentary serves not only as an information medium but also as a means of education and preservation of Peranakan Chinese culinary culture. By combining visual elements, narrative, and interviews, this documentary comprehensively presents historical, social, and cultural values. Therefore, this work is expected to raise public awareness of the importance of preserving culinary cultural heritage amidst modern developments.